PENGATURAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH DI KOTA DENPASAR - Yuliarta, I Gede Agus; Wairocana, I Gusti Ngurah; Sudiarta, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
Every human being has a need for a different life, and in the meeting of human needs itis require the adequate income. This situation also applies to the countries in which eachcountry there have needs that must be met. The need to finance the use of facilities andinfrastructure in the country, where infrastructure is intended for the benefit of society. Thefunds are used to fulfil the needs of the State is derived from abroad is usually acomplement to the fund, either in the form of foreign direct investment and loans madebilaterally or multilaterally. The funds raised from domestic savings obtained from thepublic, government savings or from the taxes paid by the public as a source of meetingthose needs. Taxes are another source to finance the national development in order toimprove the welfare of society. The tax is a contribution to the state (which can beenforced), which shall be payable by the payment to them under the rules do not getachievements back, which can directly appointed, and that use to finance publicexpenditures associated with the State's duty to govern.In the city of Denpasar there is a vacuum of norm, concering the regulation tax for thebuilding. The local regulation concering the tax for the building is not yet implemented.
Keywords: income, funds, taxes, and govern